Case-based radiological anatomy instruction using cadaveric MRI imaging and delivered with extended reality web technology - Nakamatsu, Nicole A.; Aytaç, Güneş; Mikami, Brandi; Thompson, Jesse D.; Davis, McKay; Rettenmeier, Christoph; Maziero, Danilo; Andrew Stenger, V.; Labrash, Steven; Lenze, Stacy; Torigoe, Trevor; Lozanoff, Beth K.; et al. (European journal of radiology, 2022)
•Modified donor and radiological information for each cadaver were used by most students (78%).•Cases were helpful (4.14 ± 1.1, 74.3%) in understanding of dissection (4.32 ± 0.9, 79.7%).•The XR presentation using z-space was used by 40.5% of the students.•Z-space use was moderately difficult (2.90 ± 1.0, 23%) but improved understanding (2.90 ± 1.0, 23%). Extended reality (XR) technology enhances learning in medical education. The purpose of this study was to develop and apply a case-based approach for teaching radiological anatomy utilizing XR technology for improved student exploration and engagement. The workflow consisted of MRI scanning cadavers followed by radiological, pathological, and anatomical assessment, and finally case presentation based on XR visualizations and student interaction. Case information (Subject, History, and Physical Exam) was presented to student groups who generated and recorded hypotheses using Google Forms. Use of all components of the system was voluntary and a total of 74 students responded to the survey request (response rate = 95%). Assessment of the experience was conducted through a qualitative survey comprising four Likert scale questions (1–5, 1 lowest), three binary questions, and open-ended comments. Mean, standard deviation, and overall agreement (mean ± SD, OA) showed that students found MRI scans of cadavers to be helpful for dissections (4.14 ± 1.1, 74.3%) and provided an understanding of relevant anatomy (4.32 ± 0.9, 79.7%), while 78.4% of students used the DICOM viewer to visualize scans of cadavers. The difficulty of use was found to be average (2.90 ± 1.0, 23%). zSpace visualizations were used by 40.5% of students, generally agreeing that an understanding of spatial relationships improved as a result (3.60 ± 1.0, 43.2%). More case-based sessions were favored by 97.3% of students. Results suggest that cadaveric MRI radiological visualization and XR technology enhance understanding of case-based anatomical dissections and encourage student exploration and engagement.